THE TECHNOLOGICAL CALCULATION OF THE REACTOR OF HYDROTREATING OF DIESEL FUEL AS A SYSTEM WITH THE DISTRIBUTED PARAMETERS - K. I. Netsvetaeva; A. Y. Voronin (Современная наука и инновации, 2022)
The article provides a dependence of commodity diesel fuel quality on temperature in the reactor with a motionless layer of the catalyst and offers a new method of a temperature control field in the reactor. The mathematical calculation proves the correctness of a choice of the sizes and parameters of reactor for describing the mathematical model which is necessary for experimental research